2006
DOI: 10.1073/pnas.0604728103
|View full text |Cite
|
Sign up to set email alerts
|

An 85-aa segment of the GB virus type C NS5A phosphoprotein inhibits HIV-1 replication in CD4 + Jurkat T cells

Abstract: GB virus type C (GBV-C) is an apparently nonpathogenic virus that replicates in T and B lymphocytes and is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 50 publications
6
115
1
4
Order By: Relevance
“…Another explanation of why infection with GBV-C isolates leads to suppression of a broader range of HIV-1 isolates might be due to the fact that clinical GBV-C isolates mediate HIV-1 interference not only via the E2 pro- tein. This is supported by earlier studies, where it has been reported that GBV-C infection stimulates the induction of HIV-inhibitory chemokines in primary lymphocytes and that the expression of GBV-C NS5A in lymphoid cell lines can efficiently reduce HIV-1 susceptibility (14,34,35). During the budding process retroviruses acquire a lipid envelope derived from the plasma membrane of the host cell that contains mainly cellular lipids, viral envelope, and cellular surface proteins (5,23).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another explanation of why infection with GBV-C isolates leads to suppression of a broader range of HIV-1 isolates might be due to the fact that clinical GBV-C isolates mediate HIV-1 interference not only via the E2 pro- tein. This is supported by earlier studies, where it has been reported that GBV-C infection stimulates the induction of HIV-inhibitory chemokines in primary lymphocytes and that the expression of GBV-C NS5A in lymphoid cell lines can efficiently reduce HIV-1 susceptibility (14,34,35). During the budding process retroviruses acquire a lipid envelope derived from the plasma membrane of the host cell that contains mainly cellular lipids, viral envelope, and cellular surface proteins (5,23).…”
Section: Discussionsupporting
confidence: 69%
“…Two viral proteins have been shown to inhibit HIV-1 replication in vitro. Xiang et al demonstrated that expression of NS5A induces the expression of SDF-1 and the downregulation of CXCR4 (35,38). Previously, we demonstrated that the GBV-C envelope glycoprotein E2 is involved in HIV-1 inhibition (13).…”
Section: Gb Virus C (Gbv-c) a Positive-strand Rna Virus Of The Flavimentioning
confidence: 99%
“…Plasmid pTRE2/A3G was created by PCR amplification of an ϳ1.2-kb DNA fragment from pHA-A3G, followed by insertion of the fragment into the pTRE2-Hyg-GFP expression vector. This plasmid was modified from the original pTRE2-Hyg vector by insertion of the encephalomyocarditis virus internal ribosomal entry site element to direct translation of green fluorescent protein (GFP) (30). WT and mutant viruses were obtained by transfecting 293T cells with infectious plasmids using calcium phosphate precipitation as previously described (2).…”
Section: Methodsmentioning
confidence: 99%
“…Latent herpesvirus infection may make HIV susceptible to acyclovir, which fails to exhibit anti-HIV effect in cells singly infected with HIV (53). Other viruses, both DNA- and RNA-containing viruses, may also interfere with HIV reproduction (33,84,90). Nonapparent persistent infection with a virus (e.g., SV5) may modulate the innate immune system of host cells, altering thereby reproduction of another virus in these cells (93).…”
Section: Discussionmentioning
confidence: 99%